On the Evaluation of Clipping Effects in Massive MIMO-OFDM Systems - Guerreiro, João (2016)
The combination of massive multiple input multiple output (MIMO) schemes with orthogonal frequency division multiplexing (OFDM) modulations are being considered for 5th generation (5G) wireless broadband systems. However, both the high complexity associated to massive MIMO transceivers as well as the amplification problems of OFDM constitute important drawbacks of such combination. In this paper we propose a reduced complexity, energy efficient massive MIMO OFDM scheme. For that purpose, we consider a maximal ratio transmit (MRT) technique combined with a simple time-domain clipping operation. We present an analytical method for obtaining both the power spectral density (PSD) of the transmitted signals, as well as the signal-to-interference (SIR) at the detection level. It is shown that having a large number of transmit antennas not only provides the known power and capacity gains, but also increases the robustness to nonlinear distortion effects.